A Dual-Wavelength Ocean Lidar for Vertical Profiling of Oceanic Backscatter and Attenuation - Kaipeng Li; Yan He; Jian Ma; Zhengyang Jiang; Chunhe Hou; Weibiao Chen; Xiaolei Zhu; Peng Chen; Junwu Tang; Songhua Wu; Fanghua Liu; Yuan Luo; et al. (Remote Sensing, 2020)
Ocean water column information profiles are essential for ocean research. Currently, water column profiles are typically obtained by ocean lidar instruments, including spaceborne, airborne and shipborne lidar, most of which are equipped with a 532 nm laser; however, blue wavelength penetrates more for open ocean detection. In this paper, we present a novel airborne dual-wavelength ocean lidar (DWOL), equipped with a 532 and 486 nm laser that can operate simultaneously. This instrument was designed to compare the performance of 486 and 532 nm lasers in a single detection area and to provide a reference for future spaceborne oceanic lidar (SBOL) design. Airborne and shipborne experiments were conducted in the South China Sea. Results show that—for a 500-frame accumulation—the 486 nm channel obtained volume profiles from a depth of approximately 100 m. In contrast, the vertical profiles obtained by the 532 nm channel only reached in a depth of 75 m, which was approximately 25% less than that of 486 m channel in the same detection area. Results from the inverse lidar attenuation coefficient <semantics>α(z)</semantics> for the DWOL show that the maximum value of <semantics>α(z)</semantics> ranged from 40 to 80 m, which was consistent with the chlorophyll-scattering layer (CSL) distribution measured by the shipborne instrument. Additionally, <semantics>α486(z)</semantics> decreased for depth beyond 80 m, indicating that the 486 nm laser can potentially penetrate the entire CSL.